Effects of added whey protein aggregates on textural and microstructural properties of acidified milk model systems. (November 2016) - Liu, Guanchen; Buldo, Patrizia; Greve, Marie T.; Nielsen, Søren B.; Nielsen, Jacob H.; Ipsen, Richard
Abstract: Non-fat milk model systems containing 5% total protein were investigated with addition of micro- or nanoparticulated whey protein at two levels of casein (2.5% and 3.5%, w/w). The systems were subjected to homogenisation (20 MPa), heat treatment (90 °C for 5 min) and chemical (glucono-delta-lactone) acidification to pH 4.6 and characterised in terms of denaturation degree of whey protein, particle size, textural properties, rheology and microstructure. The model systems with nanoparticulated whey protein exhibited significant larger particle size after heating and provided acid gels with higher firmness and viscosity, faster gelation and lower syneresis and a denser microstructure. In contrast, microparticulated whey protein appeared to only weakly interact with other proteins present and resulted in a protein network with low connectivity in the resulting gels. Increasing the casein/whey protein ratio did not decrease the gel strength in the acidified milk model systems with added whey protein aggregates.